Assessing the Extent to Which Current Clinical Research is Consistent with Patient Priorities: A Scoping Review Using a Case Study in Patients on or Nearing Dialysis - Min Jun; Braden Manns; Andreas Laupacis; Liam Manns; Bhavdeep Rehal; Sally Crowe; Brenda R. Hemmelgarn (Canadian Journal of Kidney Health and Disease, 2015)
Purpose of review: There is growing acknowledgement that engaging patients to identify their research priorities is important. Using a case study of patients on or nearing dialysis, we sought to assess the extent to which recently completed and ongoing clinical research was consistent with priorities identified by patients, caregivers, and clinicians. Sources of information: Over a 4-year sampling frame (January 2010 to December 2013), we systematically searched the medical literature (top 5 nephrology and top 10 general medicine journals accessed through MEDLINE via Ovid), international randomized controlled trial (RCT) registries, and national government and kidney research funding organizations (Canada, U.S., Australia, and U.K.) for published clinical studies, registered RCTs, and funded clinical studies, respectively. Published clinical studies, registered RCTs, and funded clinical studies were categorized as to whether or not they were consistent with the top 10 research priorities identified by patients, their caregivers, and clinicians in a recent comprehensive research priority setting exercise. Findings: The search yielded 4293 published articles, 688 RCTs, and 70 funded studies, of which 1116 articles, 315 RCTs, and 70 funded studies were eligible for inclusion. Overall 194 published studies (17.4 %), 71 RCTs (22.5 %), and 15 funded studies (21.4 %) included topics consistent with the top 10 research priorities identified by patients. Four of the top 10 research priorities, including strategies to improve the management of itching, increase access to kidney transplantation, assess the psychosocial impact of kidney failure, and determine the effects of dietary restriction received virtually no attention. Limitations: The top 10 priorities we used to categorize included studies were identified by Canadian patients, caregivers, and clinicians. The top research priorities may vary across different countries. The proportion of published studies that are consistent with the top 10 priorities could be different in nephrology journals with lower impact factors. Studies related to kidney transplantation and the psychosocial impact of kidney failure may have been published in journals not included in our search strategy. Implications: The majority of recently completed or ongoing clinical studies in patients on or nearing dialysis do not address the top research priorities of patients, raising concerns that current clinical research may not be meeting the needs of the ultimate consumer, in this case, patients on or nearing dialysis. Greater involvement of patients in research is required to bridge the gap between research and patients' needs.